USE OF INNOVATIVE TECHNOLOGIES AND FEATURES OF THE CONCERT MASTER’S WORK IN THE CONDITIONS OF DISTANCE LEARNING - Врубель, Г.Ф. (SWorldJournal, 2022)
The abstracts outline the main directions of the accompanist’s work and analyze the features of the use of innovative technologies in distance learning. Emphasis is placed on software that can be used for group and individual lessons: Zoom, Skype, GoogleM